The Independence of Prosecutors and Government Accountability - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2017)
Prosecutors are immensely influential in every judicial system, yet very little is known about the impact of their organization. Here we ask two questions: (1) whether crimes committed by public officials are more likely to be prosecuted when prosecutors are independent, and (2) whether this effect depends on the integrity of the prosecutors themselves. We employ a novel indicator for prosecutorial independence based on data from the World Justice Project to answer these questions. We find that prosecutorial independence favors the prosecution of different types of public officials and this effect is conditional on the level of prosecutorial corruption. For police officers, we find that prosecutorial independence is not decisive, but prosecutorial corruption matters for whether suspected misconduct is likely to be prosecuted.
Keywords: D73; H11; K40; K42; 330; Prosecutorial Independence; Prosecutorial Corruption; Government Accountability